Comparison of Patient Radiation Dose for 128-Row Multidetector Coronary Computed Tomography Angiography by Prospective Versus Retrospective ECG-Triggering Techniques - Chaosuwannakit, Narumol; Makarawate, Pattarapong (Srinagarind Medical Journal, 2013)
Background and objective: To patient radiation dose in a group of patients who underwent 128-row multidetector coronary computed tomography angiography (CCTA) performed with prospective electrocardiographic (ECG) triggering with radiation dose in a group of patients who underwent CCTA performed with retrospective ECG-triggering. Method: We performed a retrospective review of 233 consecutive patients referred for CCTA. CCTAs was performed using different scanning protocols depend on patient’s heart rate. The effective radiation dose was calculated for each patient. Results: Depending on different dose saving techniques and heart rate, the effective whole-body dose of a cardiac scan ranged from 2.8 to 11.5mSv. Prospective ECG-triggering (PT) has the greatest potential to reduce the effective dose to 64 %, compared to a comparable scan protocol with retrospective ECG-triggering (RT). Conclusion: Due to this broad variability in radiation exposure of coronary CTA, the radiologist and technician should be aware of the different dose reduction strategies. Keywords: Radiation exposure, Coronary CTA, CT angiography, Computed Tomography